Pelatihan Pembuatan Sistem Informasi Penjualan Produk Tani Untuk Kelompok Tani Muda di Desa Labulia - Rosanensi, Melati; Sakti, Lanang; Santoso, Heroe; Madani, Miftahul; Suriyati; Mayadi (Insan Kreasi Media, 2024)
As time goes by, information systems are still very much needed, both for individuals and groups. Information systems are still very reliable, especially for sales, such as selling agricultural products to Indonesian young farmers' associations. The Indonesian Young Farmers Association is a community that sells and produces various agricultural products such as fertilizers, pesticides, medicines, seeds, fruits, vegetables, spices, and food crops. The Indonesian Young Farmers Association is one of the farmer groups located in rural areas. So far the Indonesian Young Farmers Association still uses a conventional system, namely customers who come to their place of business, so buyers have to go to the place where they buy agricultural products and customers need energy to choose the goods or agricultural products they want to buy, and to face intense competition they must have a marketing strategy. Different from its competitors, this requires an information system that can provide information about products to customers quickly and accurately. This research uses the waterfall method which starts from analysis, design, implementation, testing, and maintenance. Results From the trial, a tabulation of 100% was obtained which stated that they strongly agreed that the system that had been created was suitable and could be implemented in the Farmer Product Sales Information System at the Indonesian Young Farmers Association for village progress.